Recent Advances in the Development of Type 2 Sodium-Glucose Cotransporter Inhibitors for the Treatment of Type 2 Diabetes Mellitus - Estrada, Ana K.; Delgado-Maldonado, Timoteo; Lara-Ramírez, Edgar E.; Martínez-Vázquez, Ana Verónica; Ortiz-Pérez, Eyra; Paz-González, Alma D.; Bandyopadhyay, Debasish; Rivera, Gildardo (Mini Reviews in Medicinal Chemistry, 2022)
Background: Type 2 diabetes mellitus (T2DM) is one of the most serious and prevalent diseases worldwide. In the last decade, type 2 sodium-glucose cotransporter inhibitors (iSGLT2) were approved as alternative drugs for the pharmacological treatment of T2DM. The anti-hyperglycemic mechanism of action of these drugs involves glycosuria. In addition, SGLT2 inhibitors cause beneficial effects such as weight loss, a decrease in blood pressure, and others. Objective: This review aimed to describe the origin of SGLT2 inhibitors and analyze their recent development in preclinical and clinical trials. Results: In 2013, the FDA approved SGLT2 inhibitors as a new alternative for the treatment of T2DM. These drugs have shown good tolerance with few adverse effects in clinical trials. Additionally, new potential anti-T2DM agents based on iSGLT2 (O-, C-, and N-glucosides) have exhibited a favorable profile in preclinical evaluations, making them candidates for advanced clinical trials. Conclusion: The clinical results of SGLT2 inhibitors show the importance of this drug class as new anti-T2DM agents with a potential dual effect. Additionally, the preclinical results of SGLT2 inhibitors favor the design and development of more selective new agents. However, several adverse effects could be a potential risk for patients.
Keywords: C-glycosides